Bond slip model of interface between concrete and fiber-reinforced polymer plate using finite element - Mohd Snin, Mohd Amirul (2014)
The bond between Fiber Reinforced Polymer (FRP) plate and concrete surface has shown significant effect on the behavior of strengthened Reinforced Concrete (RC) beam. Therefore, an Intermediate Crack (IC) debonding resistance which depends on the interface between FRP plate and the concrete surface remains as the main concern in designing RC beam strengthened with FRP plate. This research is to develop the bond slip model between the interface of FRP plate and concrete surface and to validate the model by carrying out experimental pull-out test. In the experimental works, two types of FRP installation have been used, namely Externally Bonded (EB) and Near Surface Mounted (NSM) methods. The sizes of FRP plate that were used for both methods were (width (mm) x thickness (mm)): 10x 1.2 , 10x 2.4, 10x3.6, 20x1.2 , 20x 2.4, 30x1.2 , 30x 2.4 and 30x3.6. A total of sixteen samples were subjected to the pull-out test and the results were added with the existing published data to develop the new proposed bond slip model, which was then applied into the finite element model of RC beam strengthened with FRP plate. For validation purposes, comparison of IC debonding resistance was made between the pull-out test using a new bond slip model and the existing bond slip model derived by Seracino et al. (2007a). It was found that the pull-out test with the new bond slip model achieved very close results as compared to the bond slip model by Seracino et al. (2007a). On the other hand, comparison was also made in terms of IC debonding resistance between the experiment and finite element model of RC beams strengthened with FRP plate. The IC debonding resistance was determined from modeling of Bodin’s work by using the new bond slip model for EB method. The results show that the maximum percentage difference of IC debonding resistance obtained from finite element to the experimental results is 7.78 and 24.9 percent for beam P2 and P5.Even though the difference are not close, the model still can prove that the new bond slip model is suitable to be used in prediction of IC debonding resistance for RC beams strengthened with FRP plate.